The epistemology of testimony - Lackey, Jennifer; Sosa, Ernest (Oxford : Clarendon, 2010)
Testimony is a critical source of knowledge. This volume collects 12 essays on the topic. The contributors cover topics such as the epistemic role of testimony, liberal fundamentalism and its rivals, testimony and trustworthiness, testimony and epistemic autonomy, and many more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Analysis (Philosophy)